Pengaruh Tipe Screen Printing dengan Teknik Double Cycle Lapisan TiO2 Sebagai Elektroda Kerja Dye Sensitized Solar Cell (DSSC): Lutfi Furqoni, Agus Supriyanto, Fahru Nurrosyid - Lutfi Furqoni, Lutfi Furqoni; Agus Supriyanto, Agus Supriyanto; Fahru Nurrosyid, Fahru Nurrosyid (Jurnal Fisika dan Aplikasinya, 2025)
Dye sensitized Solar Cell (DSSC) is solar cell candidate having great potential in the future because low fabrication costs and basic material is good environmentally. This study aims to determine the effect of the type of screen on the TiO2 layer as the working electrode DSSC. The working electrode in the TiO2 based DSSC fabricated by the method of screen printing double layer. Screen used in the deposition of TiO2 has the type: T-49, T-55 and T-61. TiO2 layer in the sintering at a temperature of 5000 C. DSSC structure composed of semiconductor TiO2 tersensitasi Ruthenium dye and a platinum counter electrode. TiO2 layer was tested morphology with Digital Camera Microscopy (DCM) and thickness with Scanning Electron Microscopy (SEM), while absorbance tested with UV-Vis Spectrophotometer and the electrical properties of DSSC tested with Keithley I-V Measurenment. Based on the characterization I-V obtained the greatest efficiency in the samples deposited by screen T - 49 was 0.47% .